Relationships between family values, dominance, marital satisfaction, romantic jealousy with female aggression in Shiraz, Iran - Edalati, Ali (2010)
Female aggression is a complex pattern of behaviour that may include physical,sexual, and psychological aggression. Despite the increase in public awareness,female aggression remains high in the Iranian society. Aggression among females has negative impact on female offenders, their spouse, children and the society in general. Regardless of the consequences of female aggression and its implication to both the family and the society at large, the knowledge of the prevalence and factors that may predict aggression in the Iranian society still remains limited. The current study examined the relationship between family values, marital satisfaction, romantic jealousy and dominance with female aggression in Shiraz, Iran. The study utilized complimentary mixed method approach. Ecological systems and neo-associationistic theories were used to underscore the assumptions of the study. The respondents of the study were 337 women aged 18-58 years with records of physical and psychological aggression. The sample was selected based on proportional random sampling technique. In the second phase of the study ten women were purposively interviewed. Physical and psychological aggressions were measured using Conflict Tactics Scale (CTS) by Straus (1979). Romantic Jealousy Scale (RJS) by White (1981) was used to measure jealousy. Dominance Scale (HDS: Hamby, 1996) was used to measure dominance. Kansas Marital Satisfaction Scale (KMS: Schumm et al., 1986) was used to measure marital satisfaction and Iranian family values Scale (Kazeruni, 2005) was used to measure Iranian traditional family values. Descriptive statistics, t-test, Pearson product moment correlation and regression analysis were used in the study. Complimentary mixed method approach was used to combine the findings from both the quantitative and qualitative approach. Semi-structure interview technique was used to collect the qualitative data. The findings of the study using complimentary mixed method approach indicated that the level of female psychological aggression was higher than physical aggression scores. Findings further revealed that marital satisfaction, romantic jealousy and female dominance were significantly correlated with female physical and psychological aggression. The results also revealed significant correlations between family values and psychological aggression. Multivariate Regression suggested that of the four predictor variables examined in the study (family values, marital satisfaction, romantic jealousy and dominance) only romantic jealousy and marital satisfaction significantly explained psychological aggression. However, only marital satisfaction significantly explained physical aggression. Generally, the total model explained 22.6% variance in psychological aggression and 15.4% for physical aggression. The results of the complimentary mixed method approach revealed that marital satisfaction, romantic jealousy and dominance have relationship with both physical and psychological aggression. More so, family values and female psychological aggression also showed significant relationship using the approach. The findings of the study provide support for the Ecological systems and neo-associationistic theory revealing that female aggression maybe caused by varying degrees of influence and human interaction in the society. The study recommended that future research may examine female aggression longitudinally to enhance results.